Efforts to improve the quality of narrative writing in indonesian language learning through media picture storybooks in grade iv students - Hastuti, Enny (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to improve the reading and writing achievement of Indonesian language in fourth grade students of SD Negeri 1 Mendak, Delanggu by using the syllable reading method. This type of research is a stage research, namely planning, implementation, observation and reflection. The research subjects were fourth grade students of SD Negeri 1 Mendak, 2020/2021 academic year, totaling 20 students. Data collection techniques through student activity observation sheets and assessment sheets. The criteria for the success of reading and writing achievement actions are with a completion limit of 66 (KKM = 66). The results showed that there was an increase in Indonesian reading achievement in the Pre-Cycle, Cycle I and Cycle II holdings. In the Pre-Cycle test scores the class average was 68.2 and students who scored ≥ 70 amounted to 7 students with a percentage of 33.3%. In Cycle I, the class average increased to 73.4 and students who obtained a score ≥ 70 amounted to 12 students with a percentage of 61.9%. For Cycle II, there was also a significant increase, namely the class average to 78.7 and students getting a score ≥ 70 amounted to 17 students with a percentage of 85.7%. Based on these results, it can be concluded that the use of the syllable reading method can improve the reading achievement of fourth grade students of SD Negeri 1 Mendak in the 2020/2021 academic year.